(untitled) (Revista de Ciências Agroveterinárias, 2020)
In bovines, fore and hind lateral claws are larger than the medial claws and the heel are deeper and the sole thicker. On this anatomical basis, we hypothesized that it must imply a form (size+shape) asymmetry of the digits. To test this hypothesis, we studied the acropodiums (digital series) of 15 young bovines belonging to Brown Pyrenean breed, irrespective of the gender. Dorso-plantar radiographies were obtained for each hindlimb and the form was studied in a sample of 30 hindlimbs (15 right and 15 left). Images were studied by geometric morphometric methods. A set of 7 paired landmarks on medial and lateral digital series and one axial landmark was used for the study. Lateral and medial digits were uneven both in size and shape, expressing both fluctuating and directional asymmetries. Directional asymmetries would suggest a different function in weight bearing. We hypothesize lateral digits serve to stabilize the centre of gravity to a greater extent than medial digits. These findings prompt careful reassessment of the function of each of the digital series during standing and during locomotion in future researches.